The Influence of Innovation, Planning and Distribution Factor in Improving Supply Chain Management Performance of Subsidized Fertilizer in Indonesia - Sahim, Aswin Naldi (2017)
Supply chain (SC) increasingly perceived as a critical variable for enhancing business execution.Because of that, the supply chain activities need to be optimized and this can be done through the supply chain management (SCM). This study has two key objectives: to reveal the influence of government policy in terms of planning and to check the reliability of distribution and innovation factors on the performance of the supply chain management of subsidized fertilizer in Indonesia.A total of 800 questionnaires have been distributed to the respective sample location, and a number of 587 or 73% successfully returned.Furthermore, the data from 513 respondents was analyzed using Structural Equation Modeling (SEM).The result shows that the government policy in terms of plan and the reliability of the distribution has direct and significant effect on performance management supply chain of subsidized fertilizer.However, although there is no direct influence on the performance of supply chain management, the factor of innovation indeed plays an important role because it determines the success of plan and reliability of the distribution. Moreover, the reliability of the distribution are acting as a mediator between the factors of innovation with the full performance of supply chain management. To improve the performance of supply chain management of subsidized fertilizer in Indonesia, this research suggests that the government pays attention to plan and the reliability of the distribution as well as innovation factors. Due to that, the distribution of fertilizer will be more suited to its purpose at the right time with the appropriate location, type, quantity and the right quality, and at an appropriate price.In future research, the same study could be used for other subsidized commodities.